Upregulation of Oxytocin Receptor in the Hyperplastic Prostate - Li, Zhuo (Front Endocrinol (Lausanne), 2018)
Background: The etiology of benign prostatic hyperplasia (BPH) is complex, both age and androgen are thought to be important. However, the failure of androgen blockade treatments suggests other paracrine/autocrine factors involved in BPH. Oxytocin was found to have a paracrine/autocrine role in prostate in recent years. The influence of BPH on prostatic oxytocin receptor (OTR) expression has never been studied. Material and methods: A testosterone-estradiol induced rat model of BPH was employed and human hyperplastic prostate specimens were harvested. Expressions of OTR, α(1)-adrenoreceptor subtypes and nitric oxide synthase isoforms were determined via real-time RT-PCR. OTR was further analyzed with Western-Blotting and histological examination. Subsequently, rat epithelial cells, human stromal cells and epithelial cells were cultured in vitro and treated with gradient concentrations of OT from 1 to 5 days. Cell proliferation was tested by Cell Counting Kit-8 and Flow Cytometry. Results: The rat BPH model was validated with significant increased prostate weight. H-E stain revealed a different histopathology between human and rat BPH. Masson's trichrome staining demonstrated that smooth muscle (SM) cells, epithelium cells and collagen fibers were simultaneously augmented in this rat BPH model and human BPH samples. OTR mainly localized in epithelium in rat prostate whereas it mainly localized in stroma in human prostate. OTR gene was upregulated 3.3-fold in rat BPH and 3.0-fold in human BPH, along with increased expression of 2.0-fold α(1a)ARs and 3.0-fold eNOS for rat BPH and 5.0-fold α(1a)ARs for human BPH. The expression of OTR protein was upregulated 1.4-fold in rat BPH and 3.9-fold in human BPH, respectively. Increased concentrations of exogenous OT can accelerate proliferation of rat epithelial cells and human stromal cells but has no impact on human epithelial cells in vitro. Flow Cytometry showed oxytocin could significantly increase G(2)/M period cell number. Conclusions: Our novel data demonstrates a significant and previously undocumented upregulation of OTR in both rat and human BPH. Moreover, exogenous OT accelerates proliferation of rat prostate epithelial cells and human prostate stromal cells. It is suggested OTR is involved in the development of BPH and OT regulatory system could be a potential new target for the BPH treatment.